Applicability of the Foodtexture Puff Device for Rheological Characterization of Viscous Food Products. Issue 2 (April 2015) - Morren, Sofie; Van Dyck, Tim; Mathijs, Frank; Luca, Stijn; Cardinaels, Ruth; Moldenaers, Paula; De Ketelaere, Bart; Claes, Johan
Abstract The Foodtexture Puff Device (FPD) is a noncontact rheological measurement device, which applies an air pulse on the sample and measures the subsequent deformation of the sample surface with a laser distance sensor. The deformation behavior is considered as a measure for the rheological properties of the sample. The applicability of this device was studied for use on viscous food products with a broad range of rheological characteristics. In this study, sugar and fat‐based systems with a viscosity range of respectively 0.001–6.1 Pa.s and 0.01–5.9 Pa.s were tested. Comparison of the FPD with classical rheological analyses showed that the maximum deformation created by the FPD is strongly correlated to the viscosity. Hence, the FPD is well suited for measurements on sugar‐based and fat‐based systems. It is capable of providing accurate, noncontact, fast, easy and nondestructive rheological measurements on food products. Practical Applications The FPD is a new, noncontact rheological measurement device that can be used for a wide range of food products, including sugar solutions, fruit purees and concentrates, oils and fats, molten chocolate, batter, soft pastry, among others. Furthermore, more solid food products like dough can be measured accurately. The device outputs a displacement signal over time from which information can be extracted. For simple behaviors, this can be performed based on one or a few characteristic values derived from the signal. For more complex foodstuff, the signal as a whole can be used, and techniques such as partial least squares can be used to create a calibration curve that translates the full displacement signal over time into the desired rheological values. Seen the fact that measurement time is short, the FPD is suitable for in‐line as well as for R&D applications and can replace classical devices that are often time consuming and require sample preparation.